2022
DOI: 10.1097/md.0000000000028727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pursed-lip breathing and forward trunk lean positions on regional chest wall volume and ventilatory pattern in older adults

Abstract: Pursed-lip breathing (PLB) and forward trunk lean posture (FTLP) are commonly used to relieve dyspnea and improve ventilation in a rehabilitation program. However, their effect on chest wall volumes and movements in older adults without chronic obstructive pulmonary disease has never been investigated. This observational study aimed to identify the effect of combined PLB and FTLP on total and regional chest wall volumes, ventilatory pattern, and thoracoabdominal movement using in older adults. It was hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Active cycle of breathing technique (ACBT) is a specialized category of respiratory muscle training methods used to treat respiratory problems, including breathing control, thoracic expansion exercises, and the forceful exhalation technique [20][21][22]. Studies have demonstrated that respiratory control has the same impact as IMT by improving diaphragm strength[21, 23,24], hence reducing exercise-induced dyspnea in patients [25]. COPD patients can train their inspiratory muscle function with deep breathing, inspiration, passive relaxation breathing[26], active exhalation [26,27], and other methods of chest expansion and forceful expiratory technique.…”
Section: Introductionmentioning
confidence: 99%
“…Active cycle of breathing technique (ACBT) is a specialized category of respiratory muscle training methods used to treat respiratory problems, including breathing control, thoracic expansion exercises, and the forceful exhalation technique [20][21][22]. Studies have demonstrated that respiratory control has the same impact as IMT by improving diaphragm strength[21, 23,24], hence reducing exercise-induced dyspnea in patients [25]. COPD patients can train their inspiratory muscle function with deep breathing, inspiration, passive relaxation breathing[26], active exhalation [26,27], and other methods of chest expansion and forceful expiratory technique.…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of three exercises: breathing control, chest expansion exercise and forced expiratory technique [23]. While focusing on the exercise of inspiratory muscles [24][25][26], it can also signi cantly improve lung function and arterial oxygen saturation, and nally reduce the symptoms of dyspnea and improve daily physical activity [23,27]. However, when only considering the behavior of patients with exercise intervention, we found that the cognitive level of patients could not be changed, and the exercise e cacy of patients could not be stimulated [14], resulting in the initial effect of the intervention, which was generally more signi cant in the 8th week [28].…”
Section: Introductionmentioning
confidence: 99%